Domperidone and its crucial understated effects - Afzaal, Zaima; Niazi, Maryam; Bin Mobin , Muhammad (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Domperidone, widely used in Pakistan for the relief of nausea and vomiting, is an over-the-counter prokinetic drug that has become a household name in recent years. Gastroesophageal reflux disease and delayed gastric emptying are only some of the diseases that it is extensively used for owing to its promotility effects by antagonism on dopamine-2 receptors in the gut. Although associated with numerous side effects, patients are usually informed only of common side effects such as headache and weight gain, while other crucial side effects remain understated. However, the most critical concern about the use of domperidone is its established effect as a galactagogue. A trial was done on 90 women who were given domperidone which showed a significant increase in milk volume and volume percent at 14 days and 28 days (1). Recent advancements have also shown the endocrine effects of domperidone; a study conducted on 97 patients (60 men and 37 women), found elevations in prolactin levels especially amongst the male population just after 28 days of use (2). These claims are supported by multiple studies as well. Another significant concern is the potential psychiatric effects upon discontinuation of the drug. Lactating mothers may present with symptoms that can be confused with, but are clinically distinct from postpartum depression (3). The withdrawal manifestations may pose a consequential risk for mothers and infants alike. In men, the increase in prolactin levels can cause varying degrees of breast enlargement if used chronically. This adverse effect can be a cause of psychological distress. All these important aspects of the drug still remain unknown to the general public and domperidone is still being mass prescribed by physicians in Pakistan. Patients also self-medicate because it is readily available at every pharmacy without the need for a prescription (4). There appear to be no regulatory measures in place that may prevent people from over using this medication. The adverse effects associated with domperidone seem to be dose-dependent. This highlights the need for more conclusive clinical trials that may determine the optimal dose and duration of domperidone usage (5). Raising awareness about all the understated risks of domperidone use is pivotal. Healthcare providers can educate patients about signs and symptoms of galactorrhea and advise them to seek medical attention immediately if needed. Healthcare regulatory authorities can issue warnings about the safe use of domperidone. Such measures may help mitigate the risk of domperidone misuse..